(untitled) (Indo-MathEdu Intellectuals Journal, 2025)
The ability to recognize basic colors is an important cognitive aspect for children with mild intellectual disabilities, but they often face memory barriers and difficulties in distinguishing them. This study aims to examine the effectiveness of using colorful balls as a medium to improve the ability to recognize basic colors in second-grade children with mild intellectual disabilities at SLB Negeri Manekat Niki-Niki. The research method used is Classroom Action Research (CAR) carried out in two cycles, with a total of 3 students as research subjects. Data were collected through observation, interviews, tests, and documentation, and then analyzed descriptively. The research results indicate that the use of colorful ball media can improve students’ ability to recognize basic colors. The students’ average score increased from 40.50 (poor category) in cycle I to 80.85 (good category) in cycle II. This shows that colorful ball media are effective as an alternative learning tool to enhance the cognitive abilities of children with mild intellectual disabilities, particularly in recognizing basic colors. This study provides theoretical and practical implications for teachers, schools, and other researchers in developing innovative and effective teaching methods for children with special needs.